Enhancing the photocatalytic activity of BiOX (X = Cl, Br, and I), (BiO)2CO3 and Bi2O3 by modifying their surfaces with polar organic anions, 4-substituted thiophenolates. Issue 27 (30th June 2017) - Xu, Benyan; An, Yang; Liu, Yuanyuan; Qin, Xiaoyan; Zhang, Xiaoyang; Dai, Ying; Wang, Zeyan; Wang, Peng; Whangbo, Myung-Hwan; Huang, Baibiao
Abstract : Bi-based semiconductors surface-modified by polar organic molecules display extended visible light absorption and enhanced photocatalytic activity. Abstract : When its surface is modified by using polar organic anions, 4-substituted thiophenolate anions 4-Z-C6 H4 S − (Z = NO2, COOH, H, CH3, and NH2 ), the Bi-based semiconductor BiO(HCOO) was found to exhibit a greatly enhanced photocatalytic activity. To establish the generality of this phenomenon, we examined the photocatalytic activities of other Bi-based semiconductors, BiOX (X = Cl, Br, and I), (BiO)2 CO3 and Bi2 O3, by modifying their surfaces with 4-carboxythiophenolate anions (4CBTs). As observed for BiO(HCOO), it is found that the surface modification with the 4CBT anions enhances the photocatalytic activities of BiOX (X = Cl, Br, and I), (BiO)2 CO3 and Bi2 O3, and this enhancement originates from a synergetic effect between the polarity of the polar organic anions and the internal electric field of those Bi-based semiconductors. Several factors affecting the photocatalytic activity were probed in some detail, which includes the nature of the facets and the sample sizes modified by using 4CBT anions in BiOCl and (BiO)2 CO3, the structures of Bi2 O3 phases as well as the electron-withdrawing or electron-donating ability of the 4-substituent Z of 4-Z-C6 H4 S − in BiOX (X = Cl, Br, and I).